2022
DOI: 10.3389/fendo.2022.935906
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology and Bioinformatics Analysis Identifies Potential Therapeutic Targets of Paxlovid Against LUAD/COVID-19

Abstract: BackgroundCoronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has caused a pandemic in many countries around the world. The virus is highly contagious and has a high fatality rate. Lung adenocarcinoma (LUAD) patients may have higher susceptibility and mortality to COVID-19. While Paxlovid is the first oral drug approved by the U.S. Food and Drug Administration (FDA) for COVID-19, its specific drug mechanism for lung cancer patients infected with COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…It should be noted that DDIs between medications that oncologic patients often take and Paxlovid® may signi cantly affect the risk-bene t ratio or even be prohibitive of its administration [12][13][14]. Nirmatrelvir, an antiviral protease inhibitor against SARS-CoV-2, is pharmacokinetically enhanced by ritonavir, a potent CYP3A4 inhibitor, to achieve therapeutic plasma concentrations [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that DDIs between medications that oncologic patients often take and Paxlovid® may signi cantly affect the risk-bene t ratio or even be prohibitive of its administration [12][13][14]. Nirmatrelvir, an antiviral protease inhibitor against SARS-CoV-2, is pharmacokinetically enhanced by ritonavir, a potent CYP3A4 inhibitor, to achieve therapeutic plasma concentrations [25].…”
Section: Discussionmentioning
confidence: 99%
“…A post hoc analysis from the aforementioned RCT [5] showed that molnupiravir treatment of mild-to-moderate COVID-19 in non-hospitalized, unvaccinated, immunocompromised adults was safe, but the clinical bene t from its administration, although numerically substantial, did not reach statistical signi cance [8,11]. Importantly, adverse effects due to drug-drug interactions (DDI) between medications that immunocompromised patients may already be taking, and nirmatrelvir/ritonavir may impact its tolerability among patients with cancer [12][13][14]. Moreover, recently completed RCTs of both drugs showed a lack of clinical bene t from their use among low-risk patients or even vaccinated high-risk patients in the current era of Omicron variants and widespread immunity to SARS-CoV-2 [15][16][17][18] To our knowledge, no studies to date have speci cally appraised the effectiveness of molnupiravir and nirmatrelvir/ritonavir in preventing hospitalization and mortality, exclusively among patients with solid or hematologic malignancies, using appropriate, concurrent controls.…”
Section: Introductionmentioning
confidence: 99%
“…Genes targeted by metformin were collected from online databases, including SuperPred ( Ma et al, 2022 ), Pharm Mapper ( Jiao et al, 2022 ), Swiss Target Prediction ( Shang et al, 2023 ), and TargetNet ( Zhang et al, 2022c ), with “metformin” as the keyword. Uniprot database was used to identify the genes.…”
Section: Methodsmentioning
confidence: 99%